UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KARAKTER PESERTA DIDIK MELALUI KURIKULUM MERDEKA BELAJAR - Siti Muawanatul Hasanah, Anggun Nike Khotimah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2024)
It has become common for the change of individuals occupying the education minister's seat to result in the replacement of the existing curriculum. At present, the new curriculum is called the Independent Learning Curriculum, which serves as a solution to the issues of student character or morality in previous curricula, which were still topics of discussion every year. In the Independent Learning Curriculum, character education is summarized into the Pancasila Student Profile. School principals, as supervisors or leaders in their schools, will certainly be the primary pillars in implementing the transition from the existing curriculum to the new one. School principals also serve as pioneers of innovation for the advancement of education in their schools, serving as motivators and peers who can provide advice to fellow educators. These efforts will ultimately culminate in the success of school principals in imparting character education to their students.